Transformasi Digital dan Implikasinya Terhadap Hukum Ekonomi Syariah: Tren dan Adaptasi - Supiana, Nana; Saroji, Romi Putra; Muliani, Muliani (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2025)
Digital transformation through Blockchain technology, artificial intelligence (AI), and electronic payment systems has had significant implications for Islamic economic law, both as a catalyst for efficiency and as an ethical challenge. This study aims to explore how adaptation to digital technology can be carried out in order to remain in line with sharia principles, particularly justice, transparency, and the avoidance of usury and gharar. Using library research and a descriptive-analytical approach, this study reviews the literature related to digitalization trends and their impact on sharia regulations. The results show that Blockchain strengthens Sharia compliance through smart contracts and audit transparency, AI supports halal investment screening while minimizing human bias, and electronic payment systems expand Sharia financial inclusion through instant transactions and automatic zakat compliance. However, ethical challenges such as data ownership, algorithm transparency, and user privacy have also emerged, requiring harmonization with the principles of tauhid, amanah, and ihsan. This study concludes that the integration of digital technology in sharia economic law not only strengthens efficiency and compliance but also requires normative regulation, collaboration between scholars and technology experts, and strict halal certification. As a result, digital transformation has the potential to strengthen the Islamic economy, enhance institutional reputation, and ensure the sustainable welfare of the people.